Blood Gas Analysis in Neonatal Tetanus - Taslim S. Soetomenggolo; Dwi Putro Widodo; Jimmy Passat; Sofyan Ismael (Indonesian Pediatric Society, 1994)
We reviewed the results of arterial blood gas analysis in 127 patients with neonatal tetanus on admission, and in 52 of such patients on the day before they died. All patients were hospitalized at the Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta. On admission, most patients showed uncompensated metabolic acidosis. The mortality of patients wjth pH ofless than 7 was 100%. There was no significant difference between the mortality of patients with pH 7.35-7.45 and those with pH of less than 7.35. Analysis of acid-base balance indicated that ventilatory fw1ure was the most common finding in 52 patients who subsequently died. We recommend using intravenous fluid containing a combination of 5% dextrose and sodium bicarbonate with 4 : 1 (vol/vol) ratio from the fust day of hospitalization to reduce the possibility of the development of ongoing metabolic acidosis in patients with neonatal tetanus. Maintaining adequate ventilation is mandatory ln such patients.